Public-Private Partnerships and Sustainable Agricultural Development - Paul Castle (Sustainability, 2011)
Agriculture in Africa is not sustainable because average yields have been stagnating for decades due to underinvestment, especially in the development of agricultural markets, crop improvement and the sustainable management of agricultural systems. Low public sector funding for agricultural research and lack of incentives for the private sector to operate in areas where there is no market largely explain the yield gap in many food-importing developing countries. Yet, there are effective ways in which the public and the private sector could work together and jointly improve agricultural sustainability in poor countries. The public sector provides a favorable institutional environment for the development of agricultural markets and investment in rural infrastructure, facilitates local business development and funds research with local relevance. The private sector, in return, brings its considerable expertise in product development and deployment. This article illustrates how new forms of public-private partnerships (PPPs) for agricultural development can work in challenging environments. It discusses three promising examples of PPPs in which the Syngenta Foundation for Sustainable Agriculture (SFSA) is actively involved, and shows that an experimental approach can sometimes be more effective than social planning in efforts to achieve sustainable agriculture.